Analisis Musik Tangis Dilo sebagai Media Pelestarian Tradisi Meratap Suku Alas di Aceh Tenggara - Rizki Mona Dwi Putra; Elmi Novita; Abdul Rozak (Universitas Negeri Medan, 2025)
Tangis Dilo is one of the musical traditions of the Alas community in Kutacane, Southeast Aceh, which is presented in the form of lullabies with simple melodies and expressive lyrics. Tangis Dilo serves as a medium for conveying moral messages, prayers, and parents' hopes for their children, as well as a means of passing on life values. However, the tide of globalization has resulted in this tradition being practiced less and less frequently, threatening its disappearance from community life. Therefore, preservation efforts are needed to ensure its relevance amid changing times. The purpose of this study is to analyze and describe the presentation of Tangis Dilo music in an effort to preserve it as the intangible cultural heritage of the Alas community. The research uses a qualitative method with data collection techniques in the form of literature studies, direct observation, interviews with practitioners, and audio-visual documentation. The results of the study show that Tangis Dilo has distinctive musical characteristics, with a monophonic form, simple melodies with repetitive patterns, and a free rhythm that adapts to the lyrics and emotions of the singer. Its musical structure is flexible, depending on the message to be conveyed, making each performance unique. Therefore, preservation must be carried out through documentation, education, and the use of digital media to ensure that Tangis Dilo remains as the intangible cultural heritage of the Alas community.